Targeting MET in cancer therapy - Hong-Nan Mo (KeAi Communications Co., Ltd., 2017)
MET encodes a receptor tyrosine kinase c-MET for hepatocyte growth factor (HGF). The specific combination of c-MET and HGF activates downstream signaling pathways to trigger cell migration, proliferation, and angiogenesis. MET exon 14 alterations and MET gene amplification play a critical role in the origin of cancer. Several monoclonal antibodies and small-molecule inhibitors of c-MET have been evaluated in clinical trials. In patients with advanced non-small cell lung cancer, cabozantinib and crizotinib showed clear efficacy with a generally tolerable adverse events profile. In gastrointestinal cancers, most phase III trials of MET inhibitors showed negative results. In hepatocellular carcinoma, based on the encouraging results of some phase II studies, a series of phase III trials are currently recruiting patients to access the efficacy and safety of MET inhibitors. Keywords: Proto-oncogene protein c-MET, Antineoplastic agents, Protein kinase inhibitors, Molecular targeted therapy